The influence of multiple social categories on emotion perception - Craig, Belinda; Lipp, Ottmar (Academic Press, 2018)
Although the human face provides multiple sources of social information concurrently (race, sex, age, etc.), the majority of studies investigating how social category cues influence emotional expression perception have investigated the influence of only one social category at a time. Only a couple of studies have investigated how race and sex cues concurrently influence emotion perception and these studies have produced mixed results. In addition, the concurrent influence of age and sex cues on emotion perception has not been investigated. To address this, participants categorized happy and angry expressions on faces varying in race (Black and White) and sex (Experiments 1a and 1b) or age (older adult and young adult) and sex (Experiment 2). In Experiments 1a and 1b, results indicated that sex but not race influenced emotion categorization. Participants were, on average, faster to categorize happiness than anger on female, but not on male faces. In Experiment 2, both the age and the sex of the face independently influenced emotion categorization. Participants were faster to categorize happiness than anger on female and young adult faces, but not on male or older adult faces. Bayesian ANOVAs provided additional evidence that the sex of the face had the strongest influence on emotion categorization speeds in Experiment 1a and 1b, but both age and sex cues had an equal influence on emotion categorization in Experiment 2.